Effects of a false-positive result in newborn congenital hypothyroidism screening on parents in Guangxi, China - Tu, Si-Jing; Wei, Yu-Jia; Chen, Bu-Tong; Zhang, Xiao-Fei; Luo, Chao; Dong, Bai-Qing (Frontiers in Pediatrics, 2023)
Background As more than 500,000 neonates participate in newborn congenital hypothyroidism (CH) screening in Guangxi Zhuang Autonomous Region each year, the overall number of false-positive (FP) cases has increased. We aim to assess the parental stress in parents of neonates with FP CH results in Guangxi, find out the influence factors related to demographics, and provide the basis for personalized health education. Methods The parents of neonates with FP CH results were invited to participate in the FP group, and the parents of neonates with all negative results were invited to participate in the control group. The parents completed a questionnaire on demographics, knowledge of CH, and the parental stress index (PSI) in the hospital for the first time. The follow-up visits for PSI were conducted 3, 6, and 12 months afterward through telephone and online. Results A total of 258 and 1,040 parents participated in the FP and control groups, respectively. The parents in the FP group had better knowledge of CH and higher PSI scores than the parents in the control group. The result of logistic regression showed that the major influence factors related to the knowledge of CH were FP experience and source of knowledge. The parents in the FP group who were well-informed during the recall phone call had lower PSI scores than the other parents. The parents in the FP group showed decreasing PSI scores gradually in follow-up visits. Conclusion The results suggested that FP screening results may affect parental stress and parent–child relationship. FP results increased the stress on the parents and increased their knowledge of CH passively.